Genome Organization and Molecular Analysis of the Temperate Bacteriophage MM1 of Streptococcus pneumoniae - Obregón, Virginia (American Society for Microbiology, 2003)
The genome of MM1 (40,248 bp), a temperate bacteriophage from the Spain(23F)-1 multiresistant epidemic clone of Streptococcus pneumoniae, is organized in 53 open reading frames (ORFs) and in at least five functional clusters. Bioinformatic and N-terminal amino acid sequence analyses enabled the assignment of possible functions to 26 ORFs. Analyses comparing the MM1 genome with those of other bacteriophages revealed similarities, mainly with genomes of phages infecting gram-positive bacteria, which suggest recent exchange of genes between species colonizing the same habitat.